Aseptic Meningitis With Systemic Lupus Erythematosus: Case Report and Review of the Literature - Masako TSUKAMOTO; Masaki SHIMAMOTO; Takeshi TERASHIMA; Noriyuki SETA (Archives of Rheumatology, 2019)
In this article, we describe a 29-year-old female patient with a history of systemic lupus erythematosus (SLE) in remission for six years presenting with fever, headache, and arthritis. Neurological examination was normal, as were brain computed tomography and magnetic resonance imaging, but based on results of cerebrospinal fluid examination and symptoms indicating active SLE, including erythema and oligoarticular arthritis, she was diagnosed as aseptic meningitis secondary to SLE recurrence. Her symptoms promptly improved with prednisolone treatment. This case suggests that aseptic meningitis should be considered in SLE patients, even when neurological findings are equivocal.